Reliability analysis of surface mount solder joints - Yeo, Chee Keng. (2009)
The reliability of solder joints was studied through experimental and finite element analysis (FEA) approaches. A no clean surface mount process for the assembly of Plastic Quad Flat Packs (PQFPs) with 15.7 mil (0.4 mm) pitch and 256 leads was established. Samples were tested under temperature range of between negative 55 degrees celcius to 125 degrees celcius to study the microstructure change and fatigue life of solder joints. Observations of microstmcture changes such as the growth of intermetallics, grain coarsening as well as thermal fatigue cracks were made.